Incidence disparities of obstructive sleep apnea-associated lung cancer by gender; Korean National Health Insurance data analysis - Park, Marn Joon; Han, Kyung-Do; Cho, Jae Hoon; Choi, Ji Ho (Frontiers in Oncology, 2023)
Obstructive sleep apnea (OSA) is known to increase the risk of various cancers. By analyzing the Korea National Health Insurance Service (KNHIS) registry, the impact of OSA on the lung cancer incidence was analyzed in a retrospective cohort group. A retrospective cohort of adult patients newly registered with OSA in the KNHIS data from 2007 to 2017 was included and observed until December 2019 (12 years). The main outcome measure was newly diagnosed lung cancer. The control group was set with age and sex that matched those in the OSA group. The hazard ratio (HR) of OSA for lung cancer incidence showed a significantly reduced HR of 0.87 (95% CI, 0.82-0.93). The observed significance of this finding was limited to male OSA patients (HR, 0.84 (95% CI, 0.78-0.90)), while no significant association was found in female OSA patients (HR, 1.05 (95% CI, 0.91-1.21)), irrespective of their age. OSA patients have a lower risk of developing lung cancer, but this risk reduction is gender-specific, as female OSA patients do not show a reduction in hazard ratio.The authors sought to determine the incidence and hazard ratio of lung cancer in patients with OSA using a large, nationwide retrospective cohort stretching twelve years, utilizing data from the Korea National Health Insurance Service (KNHIS) database. The study incorporated analyses of subgroups based on gender and age.This study was approved by the Institutional Review Board (IRB) of Inha University Hospital (IRB no. 2022-11-004). The IRB has reviewed and approved the study design and issued an exemption for the informed consent of the study subjects. The authors adhered precisely to the research standards while being formally monitored by the IRB.